Survey And New Approach In Service Discovery And Advertisement For Mobile Ad Hoc Networks. - Seno, Seyed Amin Hosseini; Budiarto, Rahmat; Wan, Tat-Chee (Dr. Sang H. Lee, 2007)
Service advertisement and discovery is an important component for mobile adhoc communications and collaboration in ubiquitous computing environments. The ability to discover services offered in a mobile adhoc network is the major prerequisite for effective usability of these networks. This paper aims to classify and compare existing Service Discovery (SD) protocols for MANETs by grouping them based on their SD strategies and service information accumulation strategies, and to propose an efficient approach for addressing the inherent issues.